The Effect of Variation in Expansion Valve Capacity on Cooling Performance in Cold Storage Machines - I Putu Gede Krisna Mahendra Putra; Hendra Wijaksana; Made Sucipta (Natural Sciences Engineering and Technology Journal, 2023)
The rapid development of the food storage industry in Indonesia, especially for basic ingredients, is very influential in the business world, such as the business of supplying food, fresh meat, and vegetables, all of which require a storage device that can maintain the freshness and quality of the food. These various products. One example of such a tool is cold storage. The increasing demand for food products makes suppliers have to meet the great demand for food by increasing the supply of products. With such conditions, many suppliers or owners of cold storage complain that the cooling performance of cold storage is not being achieved as needed. The effect of variations of the three expansion valves shows that the 2.8 TR expansion valve has cooled, whereas the 2.8 TR expansion valve has a higher refrigeration effect, and the compressor work on the 3.7 TR expansion valve and 4.4 TR expansion valve has a significant increase. This can be caused by the increased refrigerant flow so that the compressor makes a greater effort to compress the refrigerant, and from that, the system workability (COP) has decreased. The effect of the variation of the three expansion valves shows that the expansion valve 4.4 TR has a faster decrease in room temperature, where the initial room temperature is considered uniform. The 4.4 TR expansion valve opens the valve gap earlier, and the refrigerant flow that flows is greater when the engine is started so that heat is absorbed by the evaporator faster.